Internalisasi Nilai-Nilai Kearifan Lokal Upacara Adat Grebeg Songo-Songo dalam Bidang Pendidikan di Kabupaten Trenggalek - Sukmawati, Anis (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study aims to examine the process of internalizing the values of local wisdom contained in the traditional Grebeg Songo-Songo ceremony in Trenggalek Regency, particularly in the field of education. The primary focus of this research is (1) to trace the history and origins of Grebeg Songo-Songo as a tradition of the Trenggalek community, (2) to identify the local wisdom values embedded in this traditional ceremony, and (3) to analyze how these values are internalized into the educational sector in Trenggalek. This research employs a qualitative approach, utilizing in-depth interviews, observations, and literature studies to collect data. The findings reveal that Grebeg Songo-Songo has deep historical roots as a form of appreciation from the Sumurup village community toward Tumenggung Wiraguna of Mataram for his efforts to repel a plague or epidemic in the past. The ceremony also embodies local wisdom values such as mutual cooperation, education, solidarity, and respect for nature. The internalization of these values in education is achieved through their integration into extracurricular activity curricula and collaboration between schools and local communities. These findings provide new insights into the importance of preserving local traditions as part of character building for students and cultural conservation in the modern era.